Perspectives on Academic Writing in European Higher Education: Genres, Practices, and Competences - Otto Kruse (Universitat Politècnica de València, 2013)
Academic writing in European higher education is a little explored field hidden behind fifty major language and fifty national educational systems of which it is part. The article aims at developing a perspective for studying the diversity of writing in Europe and finding a shared language for analyzing student writing. The article recaps baselines theories for the teaching of writing and reports on three important European writing traditions. The main part of the paper is devoted to three foundational conceptions for writing: The role of genres in understanding student writing, the function of writing practices for the organization of student writing and the meaning of writing competences for the teaching of writing.   RESUMEN Perspectivas sobre la escritura académica en la educación superior europea: Géneros, prácticas y competencias. La escritura académica en la educación superior europea es un campo poco explorado y oculto bajo cincuenta lenguas y otros tantos sistemas educativos nacionales que la componen. El artículo tiene por finalidad elaborar una perspectiva que nos permita estudiar la diversidad que implica escribir en Europa y desarrollar un lenguaje compartido para analizar la escritura de los estudiantes. El artículo revisa las teorías básicas en la enseñanza de la escritura y se centra en tres importantes tradiciones de escritura europeas. La parte principal del documento está dedicada a tres conceptos fundamentales para la escritura: el papel de los géneros en la comprensión de la escritura de los estudiantes, la función de las prácticas de escritura para organizar lo que escriben los estudiantes y el significado de las competencias comunicativas para la enseñanza de la escritura.